Redescription of Cryptophasa irrorata Lewin, 1805 (Lepidoptera: Gelechioidea: Xyloryctidae) - Mcmillan, Ian (Zootaxa, 2019)
To serve as a reference point for future studies of the genus Cryptophasa Lewin, 1805, the type species, Cryptophasa irrorata Lewin, 1805, is redescribed with particular emphasis on the morphology of the male genitalia.